Genome size variation in butterflies (Insecta, Lepidotera, Papilionoidea): a thorough phylogenetic comparison. (7th January 2020) - Liu, Guichun; Chang, Zhou; Chen, Lei; He, Jinwu; Dong, Zhiwei; Yang, Jie; Lu, Sihan; Zhao, Ruoping; Wan, Wenting; Ma, Guolan; Li, Jian; Zhang, Ru; et al.
Abstract: Butterflies have been of great interest to naturalists for centuries, and the study of butterflies has been an integral part of ecology and evolution ever since Darwin proposed his theory of natural selection in 1859. There are > 18 000 butterfly species worldwide, showing great diversity in morphological traits and ecological niches. Compared with butterfly diversity, however, patterns of genome size variation in butterflies remain poorly understood, especially in a phylogenetic context. Here, we sequenced and assembled the mitogenomes of 68 butterflies and measured the genome sizes ( C ‐values) of 67 of them. We also assembled 10 mitogenomes using reads from GenBank. Among the assembled 78 mitogenomes, those from 59 species, 23 genera and one subfamily are reported for the first time. Combining with published data of mitogenomes and genome size, we explored the patterns in genome size variation for 106 butterfly species in a phylogenetic context based on analyses of mitogenomes from 264 species covering six families. Our results show that the genome size of butterflies has a 6.4‐fold variation ranging from 0.203 pg (199 Mb) (Nymphalidae: Heliconius xanthocles ) to 1.287 pg (1253 Mb) (Papilionidae: Parnassius orleans ). Within families, the largest variation was found in Papilionidae (5.9‐fold: 0.22–1.29 pg), followed by Nymphalidae (4.8‐fold: 0.2–0.95 pg), Pieridae (4.4‐fold: 0.22–0.97 pg), Hesperiidae (2.2‐fold: 0.3–0.66 pg), Lycaenidae (2.6‐fold: 0.39–1.02 pg) and Rioidinidae (1.8‐fold: 0.48–0.87 pg). Our data also suggest that butterflies have an ancestral genome size of c. 0.5 pg, and some ancestral genome size increase or decrease events along different subfamilies or tribes produce the diversity of genome size variation in diverse butterflies. Our data provide novel insights into patterns of genome size variation in butterflies and are an important reference for future genome sequencing programmes. Abstract : We assembled the complete mitogenomes of 78 butterfly species. Among them, the mitogenomes of 59 species, 24 genera and one subfamily are reported for the first time. We measured the C ‐values of 67 butterfly species. Combining published data, we found that the genome sizes of 106 butterfly species have a 6.4‐fold variation (0.203–1.287 pg). We inferred that butterflies have an ancestral genome size (AGS) of about 0.5 pg, and their diverse genome sizes resulted from some AGS increase/decrease events along different subfamilies or tribes.